Analysis Of The Effect Of Customer Retention Strategy And Differentiation Strategy On Customer Lifetime Value And Customer Loyalty In SME Food In Jember Regency - Siti Juariyah; Budi Santoso; Haris Hermawan; Dwi Cahyono (UNIVED Press, 2025)
This study aims to analyze the effect of customer retention strategies and differentiation strategies on Customer Lifetime Value (CLV) and customer loyalty in small and medium enterprises (SMEs) in the food sector in Jember Regency. The research approach used is a quantitative approach with a survey method of 100 customers of Ayam Gephok Pak Giek as the object of research. Data collection was carried out through a closed questionnaire, and data analysis was carried out using the Partial Least Square (PLS) method with the help of SmartPLS software. The results showed that customer retention strategy and differentiation strategy have a positive and significant effect on customer loyalty and CLV. The findings indicate that effective customer relationship management, through the provision of memorable customer experiences and unique product offerings, is critical in increasing long-term customer loyalty and value. The practical implications of this study suggest that culinary SMEs strengthen service strategies, product innovation, and loyalty programs to retain customers and increase competitiveness in a competitive market.